2019
DOI: 10.1186/s12877-019-1324-7
|View full text |Cite
|
Sign up to set email alerts
|

The value of nonoperative versus operative treatment of frail institutionalized elderly patients with a proximal femoral fracture in the shade of life (FRAIL-HIP); protocol for a multicenter observational cohort study

Abstract: BackgroundProximal femoral fractures are strongly associated with morbidity and mortality in elderly patients. Mortality is highest among frail institutionalized elderly with both physical and cognitive comorbidities who consequently have a limited life expectancy. Evidence based guidelines on whether or not to operate on these patients in the case of a proximal femoral fracture are lacking. Practice variation occurs, and it remains unknown if nonoperative treatment would result in at least the same quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 41 publications
(34 reference statements)
0
30
0
Order By: Relevance
“…This cross-sectional questionnaire study followed the ‘Strengthening the Reporting of Observational studies in Epidemiology’ (STROBE) guidelines. The online questionnaire was programmed in LimeSurvey (Version 2.06lts) [ 25 ] and widely disseminated via the project team and FRAIL-HIP study group [ 26 ] to an extensive network of healthcare providers working in the departments of trauma surgery, orthopaedic surgery and in-hospital geriatrics, and to older people’s care physicians. Within Dutch healthcare, dedicated healthcare providers, named older people’s care physicians, in nursing homes are responsible for the care of frail older institutionalised patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-sectional questionnaire study followed the ‘Strengthening the Reporting of Observational studies in Epidemiology’ (STROBE) guidelines. The online questionnaire was programmed in LimeSurvey (Version 2.06lts) [ 25 ] and widely disseminated via the project team and FRAIL-HIP study group [ 26 ] to an extensive network of healthcare providers working in the departments of trauma surgery, orthopaedic surgery and in-hospital geriatrics, and to older people’s care physicians. Within Dutch healthcare, dedicated healthcare providers, named older people’s care physicians, in nursing homes are responsible for the care of frail older institutionalised patients.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was adapted and evaluated rigorously by the FRAIL-HIP study team until consensus was reached [ 26 ]. The pre-final version was pilot tested by six healthcare providers.…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely demonstrated that surgery provides better outcomes in terms of pain control, functional level, and medium-to long-term mortality in compromised individuals [50]. Surgery should, therefore, be performed in almost every instance with conservative management of HF being restricted to specific patient groups.…”
Section: Indications For Conservative Strategiesmentioning
confidence: 99%
“…A future strictly designed and adequately powered trial is essential. 36 We believe that in the event that such a study is conducted, then, our study is one of the largest analyses in the literature comparing contemporary methods of operative and nonoperative treatment and can be used as the basis for power calculations.…”
Section: Limitations Of This Systematic Reviewmentioning
confidence: 99%